U.S. MARSHALS : INSIDE AMERICA'S MOST STORIED LAW ENFORCEMENT AGENCY - Earp, Mike (WILLIAM MORROW, 2014)
Unlike their counterparts in the police and the FBI, U.S. Marshals aren't responsible for investigating or prosecuting crimes. They pursue and arrest the most dangerous criminal offenders on U.S. soil, an extraordinarily hazardous job often involving gun battles and physical altercations. Earp takes us back to the service's early days, explaining its creation and its role in the border wars that helped make continental expansion possible. He brings to life the gunslingers and gunfights that have made the Marshals legend, and explores the service's role today integrating federal, state, and local law enforcement agencies in the hunt for the most notorious criminals, terrorists, drug lords, and gun runners. Setting his own experiences within the long history of the U.S. Marshals service, Earp offers a moving and illuminating tribute to the brave marshals who have dedicated their lives to keeping the nation safe.